Transcriptional analysis of CRISPR I-B arrays of Leptospira interrogans serovar Lai and its processing by Cas6 - Prakash, Aman; Kumar, Manish (Frontiers in Microbiology, 2022)
In the genome of various Leptospira interrogans serovars, the subtype I-B locus of CRISPR-Cas possesses either one or multiple CRISPR arrays. In silico database (CRISPRCasdb) for predicting CRISPR-Cas reveals seven CRISPR arrays in L. interrogans serovar Lai positioned between the two independent cas-operons. Here we present the redefined repeat-spacer boundaries of the CRISPR subtype I-B locus of serovar Lai. Such refinement of boundaries of arrays in serovar Lai was done after comparison with the characterized array of another serovar Copenhageni and the manual analysis of CRISPR flanking sequences. Using the reverse transcription-PCR (RT-PCR), we account that the seven CRISPR are transcriptionally active in serovar Lai. Our RT-PCR and quantitative real-time PCR analysis of transcripts in serovar Lai indicated that seven CRISPR of subtype I-B transcribe together as a single precursor unit. Moreover, the cleavage of the two miniature pre-crRNA of the subtype I-B by Cas6 demonstrates the biogenesis of the expected size of mature crRNA essential for the guided interference of foreign DNA. This study features insight into transcription direction and the crRNA biogenesis in serovar Lai essential for RNA-mediated interference of invading nucleic acids.